METHODOLOGY FOR THE DEVELOPMENT OF 4C MODEL SKILLS IN STUDENTS OF PRESCHOOL EDUCATION - Dildora Dоniyоrоva (Bright Mind Publishing, 2026)
This article examines the methodological foundations for developing skills based on the 4C model (critical thinking, creativity, communication, and collaboration) among students studying in the field of preschool education. The issues of preparing future educators for professional activity through the use of innovative educational technologies, interactive methods, and practical training are analyzed. The research findings demonstrate the significant role of the 4C model in shaping the professional competence of future preschool teachers.
Keywords: 4C model, preschool education, professional competence, creativity, students, critical thinking, interactive methods.